AVALIAÇÃO DAS ALTERAÇÕES DENTOESQUELÉTICAS DE PACIENTES COM MÁ OCLUSÃO DE CLASSE II DE ANGLE, TRATADOS COM O APARELHO REGULADOR DE FUNÇÃO DE FRÄNKEL (RF-2). - Santos Júnior, José Antônio dos (2006)
This research aimed at to study in retrospect through x-rays in front norm and models of plaster the alterations dentoesqueléticas of patients with Malocclusion of Class II, 1st division, divided in two groups: Treated group, constituted of 28 patient, being 13 patient male and 15 female, treaties with apparel regulator of function of Fränkel - 2 (RF-2), for an active period of 1,5 years; Group Controls: constituted of 28 patient, being 12 male and 16 female, that you/they were not submitted the any treatment during the 1,5 year-old longitudinal attendance. The sample of this study consisted of 112 telerradiografias of front norm and 112 equal of models of plaster, 56 obtained to he beginning (T1) and 56 at the end of the observation (T2). After the statistical analysis of the obtained measurements , it was ended that there were result in significant alterations statistically in all the analyzed measures and RF-2 had direct performance in the variables: upper distance and lower inter-molar s distance (x-rays and models), palatine depth, maxillary width and lower anterior facial height.